USAHA RENTAL MOBIL DITINJAU DARI EKONOMI ISLAM (STUDI KASUS ODE-ODE REVOLUSI RENTAL CAR KENDARI) - Devi Lestari; Ambo Wonua Nusantara; Muhammad Nur Afiat (Universitas Halu Oleo, 2022)
The purpose of this study was to determine the application of car rental carried out by the Ode-Ode Revolution Car Rental Kendari in terms of Islamic Economics. The data analysis used in this research is inductive qualitative. The results of this study indicate that the lease has been running according to Islamic law, even leasing is prescribed in Islam. However, in the implementation of leasing at Ode-Ode Rental there is a deviation made by the tenant which we can see in the risk of accidents described previously, where the tenant cannot afford the damage to the car he experienced in accordance with the rental agreement. So that there is a deviation in the practice of renting in the Revolutionary Orders of Car Rental Kendari which is not in accordance with Islamic Economics, in Islamic Economics this practice is strictly prohibited because it has harmed other people, here we can see deviations that lead to a violation of the agreement that has been agreed upon. between the two parties between the business owner (leasing) and the tenant.